2014
DOI: 10.1021/ic5006314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Approaches to Redox Innocence of Ligands in Uranyl Complexes: What Is Formal Oxidation State of Uranium in Reductant of Uranyl(VI)?

Abstract: Redox behavior of [UO2(gha)DMSO](-)/UO2(gha)DMSO couple (gha = glyoxal bis(2-hydroxanil)ate, DMSO = dimethyl sulfoxide) in DMSO solution was investigated by cyclic voltammetry and UV-vis-NIR spectroelectrochemical technique, as well as density functional theory (DFT) calculations. [UO2(gha)DMSO](-) was found to be formed via one-electron reduction of UO2(gha)DMSO without any successive reactions. The observed absorption spectrum of [UO2(gha)DMSO](-), however, has clearly different characteristics from those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 78 publications
6
47
0
Order By: Relevance
“…Also observed in this voltammogram is a broad, poorly defined irreversible oxidation at E p,a = + 0.09 V (vs. Fc/Fc + ) which is not observed at low scan rates, indicating the instability of this species. Given that the metal is in its highest oxidation state, it can be assigned as ligand based; we have observed similar behavior in the uranyl thiocyanate analogue (E p,a = + 0.30 V vs. Fc/Fc + ) and extends the family of uranyl coordinated to redox non-innocent ligands [11,32]. would be predicted to be quite unstable as it is now established that good π-donors and/or sterically bulky groups in the equatorial plane are required for stabilization of this unusual oxidation state [27,28]; although, there is evidence for the kinetic stabilization of the [UO2] + ion in ionic liquids [29][30][31].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Also observed in this voltammogram is a broad, poorly defined irreversible oxidation at E p,a = + 0.09 V (vs. Fc/Fc + ) which is not observed at low scan rates, indicating the instability of this species. Given that the metal is in its highest oxidation state, it can be assigned as ligand based; we have observed similar behavior in the uranyl thiocyanate analogue (E p,a = + 0.30 V vs. Fc/Fc + ) and extends the family of uranyl coordinated to redox non-innocent ligands [11,32]. would be predicted to be quite unstable as it is now established that good π-donors and/or sterically bulky groups in the equatorial plane are required for stabilization of this unusual oxidation state [27,28]; although, there is evidence for the kinetic stabilization of the [UO2] + ion in ionic liquids [29][30][31].…”
Section: Resultssupporting
confidence: 53%
“…Also observed in this voltammogram is a broad, poorly defined irreversible oxidation at Ep,a = + 0.09 V (vs. Fc/Fc + ) which is not observed at low scan rates, indicating the instability of this species. Given that the metal is in its highest oxidation state, it can be assigned as ligand based; we have observed similar behavior in the uranyl thiocyanate analogue (Ep,a = + 0.30 V vs. Fc/Fc + ) and extends the family of uranyl coordinated to redox non-innocent ligands [11,32]. …”
Section: Resultssupporting
confidence: 53%
“…As a consequence of coordination complex formation, varied redox behaviour is feasible . However, the electronic structure or bonding characteristics of uranyl coordination complexes is less well understood in non‐aqueous solution with relatively few studies reported . Moreover, organic multi‐dentate ligands are intriguing and often interfere with the redox properties of the uranyl cation when they have highly conjugated alternating double bonds .…”
Section: Introductionmentioning
confidence: 99%
“…This ligand again exhibits non‐innocent behaviour and traps the incoming electron to form a di‐anionic radical species. As a consequence, the oxidation state of the U‐atom remains (VI) and no reduction is observed at the U‐atom . In addition, uranyl compounds containing iminoquinone ligands in the coordination sphere have been reported to exhibit redox‐active character and during the course of the redox events the U‐center remains unaffected in its ‘VI’ oxidation state .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation